Komunikasi Nonverbal dalam Mengembangkan Konsep Diri pada Siswa Taman Kanak-Kanak (TK) Nanggala Surabaya - Aprilia Citra Prameswari; Ainur Rochmaniah (Universitas Muhammadiyah Sidoarjo, 2016)
The concept itself was very important in human life because one's understanding about themselves would determine and guide the behavior in various situations. This study aimed to describe nonverbal communication in developing self-concept in Nanggala Surabaya Kindergarten. This type of research was qualitative description. Subjects were teachers, students and parents. Key informant was head of Nanggala Surabaya Kindergarten. Data collection techniques used observation, interviews, and documentation. While the technique of analyzing data used a model of Miles and Huberman through data reduction, data presentation, and conclusion. The results showed that nonverbal communication was done by teacher to students in developing self-concept included six classifications were kinesthetic message, gestural message, proksemik message, artifactual message, paralinguistic message, touches and smells message. While, the concept of self-developed in Nanggala Surabaya Kindergarten was the concept of the physical self, moral-ethical self-social, and family pride.